A Mitsunobu reaction to functionalized cyclic and bicyclic N-arylamines. Issue 3 (17th January 2018) - Gill, Daniel M.; Iveson, Matthew; Collins, Ian; Jones, Alan M.
Graphical abstract: Highlights: An unexpected Mitsunobu route to N -arylated azacycles. Mitsunobu cyclodehydration versus intramolecular cyclisation investigated. Reaction scope, ring size, steric and p Ka effects studied in model systems. Abstract: The scope of an unexpected Mitsunobu cyclisation to prepare N -arylated F sp 3 -enriched azacycles was investigated. In the current study, we have identified whether a p Ka-dependent Mitsunobu cyclodehydration or a p Ka-independent Mitsunobu intra molecular reaction was in operation. A Mitsunobu reaction, creating a leaving group, followed by intra molecular nucleophilic displacement was determined to be the dominant pathway.